Ichthyofaunal Diversity of Godavari River at Mudgal Tq. Pathri, Dist. Parbhani - Rankhamb*, S.V. (Recent Research in Science and Technology, 2011)
Ichthyofaunal studies were undertaken during July 2009- March 2010. Present paper deals with the variety of fresh water fishes in Godavari River at Mudgal Tq. Pathri, Dist. Parbhani. The results of present investigation reveal the occurrence of 26 fish species belonging to 05 orders, 07 families and 15 genera. The members of Order Cypriniformes were dominated by 15 species followed by Siluriformes with 05 species, Channiformes 04 Species, and Mastacembaliformes 01, Perciformes 1 species.